Maternal Health Coping Strategies of Migrant Women in Norway - Berit Viken; Anne Lyberg; Elisabeth Severinsson (Nursing Research and Practice)
The aim of the study was to explore the maternal health coping strategies of migrant women in Norway. The ethnic and cultural background of the Norwegian population have become increasingly diverse. A challenge in practice is to adjust maternal health services to migrant women’s specific needs. Previous studies have revealed that migrant women have difficulty achieving safe pregnancies and childbirths. Data were obtained by means of 17 semistructured interviews with women from South America, Europe, the Middle East, Asia, and Africa. Qualitative content analysis was employed. One overall theme is as follows: keeping original traditions while at the same time being willing to integrate into Norwegian society, and four themes emerged as follows: balancing their sense of belongingness; seeking information and support from healthcare professionals; being open to new opportunities and focusing on feeling safe in the new country. The results were interpreted in the light of Bronfenbrenner’s ecological model. To provide quality care, healthcare professionals should focus on the development of migrant women’s capabilities. Adaptation of maternal health services for culturally diverse migrant women also requires a culturally sensitive approach on the part of healthcare professionals.